Inclusive Education and Identity Formation in Secondary School Students with Hearing Disabilities - Charry-Bressan, Liliana; Torres-Aya, Laura; Rodríguez-Cárdenas, Diego Efrén (Revista Electrónica Educare, 2023)
Objective. This research aimed to understand the identity configuration process in students with hearing disabilities and identify the contribution of inclusive education in this process. Method. This qualitative research used a phenomenological approach, conducting semi-structured interviews with 3 male and 2 female high school students with severe hearing impairment. Participants were from a public school in Bogotá, aged between 18 and 20 years old, and from a low socioeconomic background. The collected data was analyzed through open, axial, and selective coding according to the constant comparative method. Results. Three emerging categories were identified: “I am deaf,” “I speak another language,” and “I am capable.” The results show that students with hearing disabilities identify with the deaf community based on shared experiences of absence of hearing ability, use of sign language, stigmatization, and social vulnerability. Inclusive education contributes to the development of alternative social identities. Discussion. The emergence of capacities to seek the transformation of the exclusion conditions and the potential of inclusive education in this direction are discussed.